The Teen Toolkit: Building Confidence and Connections - Hema Dayita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Puberty is a crucial developmental phase that marks the transition from childhood to adolescence. For sixth-grade elementary school students, the biological, emotional, and social changes that occur during this period often create confusion and challenges in social interactions and the development of self-confidence. Therefore, appropriate education is needed so that students can understand the changes that occur in themselves positively. This community service project aims to provide psychoeducation about puberty and improve social skills in sixth-grade students. The method used is a participatory psychoeducational intervention-based approach through lectures, group discussions, role-playing, and self-reflection. This activity involved 64 sixth-grade students at an elementary school in Pasar Minggu, Jakarta. The material provided included the definition of puberty, the stages of puberty, signs of puberty in boys and girls, emotional and mental changes, how to care for the body during puberty, and concepts and strategies for developing social skills. The results of the activity indicate that psychoeducation about puberty and social skills can help students understand the physical and emotional changes they experience, increase self-awareness, and encourage better social interaction with peers. This program is expected to be a preventive measure in supporting the psychosocial development of children in early adolescence